Electron transport chain capacity expands yellow fever vaccine immunogenicity - Darren ZL Mok; Danny JH Tng; Jia Xin Yee; Valerie SY Chew; Christine YL Tham; Justin SG Ooi; Hwee Cheng Tan; Summer L Zhang; Lowell Z Lin; Wy Ching Ng; Lavanya Lakshmi Jeeva; Ramya Murugayee; et al. (EMBO Molecular Medicine, 2024)
Abstract Vaccination has successfully controlled several infectious diseases although better vaccines remain desirable. Host response to vaccination studies have identified correlates of vaccine immunogenicity that could be useful to guide development and selection of future vaccines. However, it remains unclear whether these findings represent mere statistical correlations or reflect functional associations with vaccine immunogenicity. Functional associations, rather than statistical correlates, would offer mechanistic insights into vaccine-induced adaptive immunity. Through a human experimental study to test the immunomodulatory properties of metformin, an anti-diabetic drug, we chanced upon a functional determinant of neutralizing antibodies. Although vaccine viremia is a known correlate of antibody response, we found that in healthy volunteers with no detectable or low yellow fever 17D viremia, metformin-treated volunteers elicited higher neutralizing antibody titers than placebo-treated volunteers. Transcriptional and metabolomic analyses collectively showed that a brief course of metformin, started 3 days prior to YF17D vaccination and stopped at 3 days after vaccination, expanded oxidative phosphorylation and protein translation capacities. These increased capacities directly correlated with YF17D neutralizing antibody titers, with reduced reactive oxygen species response compared to placebo-treated volunteers. Our findings thus demonstrate a functional association between cellular respiration and vaccine-induced humoral immunity and suggest potential approaches to enhancing vaccine immunogenicity.